Penerapan Teknologi Goat Manure Grinder Untuk Meningkatkan Kapasitas Produksi Pupuk Kandang Pada Peternakan Kambing Desa Kebobang, Kec. Wonosari, Kabupaten Malang - Erwin Komara Mindarta; Retno Wulandari; Dani Irawan; Yudha Rian Pratama; Taupik Yuhana (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Goat manure that has not been processed still has a poor texture. On the other hand, the high price of fertilizer makes it difficult for farmers to get it. However, with many farmers also having goats, of course goat manure can be an abundant source of fertilizer. The community service implementation team from the Department of Mechanical Engineering, State University of Malang (UM) answered partners' needs, by providing a solution for implementing Goat Manure Grinder technology. To achieve the goal of service, the procedures taken include 1) location survey, 2) social approach, 3) product development, 4) preparation of guidelines, 5) application of science and technology/TTG through outreach activities, introduction of tools/TTG and training; 6) follow-up through modeling and mentoring; 7) monev: progress presentation and final report, and 8) outcome fulfillment. This tool is useful for 1) smoothing goat manure, 2) can help local farmers to get cheap organic fertilizer.